A Struggle for the Soviet Future: The Birth of Scientific Forecasting in the Soviet Union. Issue 1 (2016) - Rindzevičiūtė, Eglė
Abstract : This article analyzes the development of Soviet scientific future studies after World War II, arguing that the field's theory and methods undermined the certainty of the communist future and laid the foundations for a new Soviet governmentality that acknowledged the intrinsic uncertainty of future development. The emphasis on uncertainty—but also the need for more data that could freely circulate between different branches of government and hence more transparency (glasnost')—called for radical revisions to Soviet notions of effective governance. Whereas some used future studies to criticize the actual practices of Soviet economic planning, others used this new type of expertise to extend personal influence and accumulate organizational power. Both cases, however, made it clear that Soviet governance had to accommodate the shift toward new constellations of power/knowledge in which scientific experts would play an ever-increasing role in shaping policy with regard to a fundamentally uncertain future.